PENINGKATAN PERSEPSI RESIKO MELALUI PENYULUHAN KESELAMATAN BERKENDARA PADA SISWA SMA MATER DEI PAMULANG TANGERANG SELATAN - Verdy Ananda Upa; Eka Apriliasi (JPMUJ, 2024)
Traffic accidents are one of the causes of death in adolescence and the cause of most pain in the world, especially in developing countries such as Indonesia. Risk perception is one of the important factors in developing safety behaviour. These sessions aimed to improve the perception of safety risk remains low drive that was originally to be better. Risk perception is assessed by the psychometric paradigm. The study was conducted on 150 students in September 2023 using a cross-sectional design, the primary data in the form of a questionnaire and supporting data in the form of interviews. The parameters used are Likert scale numbers 1-4. The results showed that before the activity, the perception of the students had been quite good (intermediate category) but there is still a need for improvement. Dimensions voluntariness is perceived as high compared with 8 other dimensions, meaning that students are willing to accept all the risks that exist while driving. Having conducted outreach activities increased scores on each dimension, and there are changes in the highest score on the dimensions of knowledge. Creating safety cultured behaviour then takes a strong commitment from students related to road safety, training, and dissemination of information about the applicable safety and participation of the whole society to always prioritize safety.